Stability analysis of cone-cylinder shell structures - Ismail, Mohd Shahrom (2021)
This thesis presents an evaluation of the structural performance that is relevant to the application in major industries globally (for example, oil platform, submersible structures, some compartment in aircraft/aerospace structures, shipbuilding, bridges, and others.), against failure/collapse. This structure is susceptible to buckling failures caused by excessive mechanical load action. During the design process or the buckling failure evaluation of this particular structure, initial geometric and loading imperfections are of important parameters for the analyses. Therefore, the engineers/designers are expected to well understand the physical behaviours of shell buckling to prevent unexpected serious failure in structures. In particular, it is widely reported that no efficient guidelines for modelling imperfections in particular structures are available. The consequence of inadequate design knowledge may result in (a) loss of life, (b) loss of properties and belongings, (c) costly financial implication, (d) loss of time, and (e) pollution. Therefore, knowledge obtained from the relevant works is open for updates and highly sought. In this study, the structural performance under bifurcation and collapse load, the role of ring stiffener reinforcement (such as, internal and externally stiffened), the influence of structural plasticity, and the worst-case of the imperfection for (i) cone-cylinder and (ii) cylinder-cone-cylinder shells transition have been comprehensively studied, presented and discussed. The cone-cylinder shell has also been tested experimentally to (i) axial compression and (ii) combination of axial compression and thermal. To support the experimental results, numerical simulations of cone-cylinder and cylinder-cone-cylinder transition shells are conducted by use of a finite element (FE) method based software of ABAQUS. Initial geometric imperfection techniques such as (i) eigenmode imperfection, (ii) SPLA (Single Perturbation Load approach), MPLA (Multiple Perturbation Load approach), and axisymmetric outward bulged were also adopted to further evaluate the shells worst case of imperfection under various mechanical loads. It worth noting that in this study, the establishment of the (i) design guideline and (ii) lower bound knockdown factor for a combination of shell structure assembly subjected to (i) external pressure and (ii) axial compression are presented. In particular, with a consideration of practical interest, cone-cylinder transition shell under combined load action (such as, (i) axial compression and thermal and (ii) axial compression and external pressure) were further examined through experimentation and numerical analysis. Subsequently, there is a good agreement between experimental and numerically predicted collapse load with discrepancy calculated to be within 10%. Several recommendations in the area of the structural design against collapse/failure were underline and proposed accordingly throughout the analysis.